"It's the War, Stupid!": Determinants of Retrospective Evaluations of American Presidents. Issue 4 (2nd August 2020) - King, James D.; McConnell, Jason B.
Abstract: Public opinion of presidents after they have left office is primarily the product of whether or not their administration entangled the United States in an unpopular military conflict. Using data from Gallup polls, we demonstrate that the forces of peace and prosperity drive approval ratings of former presidents when out of office but do not impact public assessments equally. A former president's popular standing is tarnished more by association with an unpopular war than it is enhanced by economic prosperity.